2002
DOI: 10.1002/art.10676
|View full text |Cite
|
Sign up to set email alerts
|

The geometric architecture of the subtalar and midtarsal joints in rheumatoid arthritis based on magnetic resonance imaging

Abstract: Objective. To compare in vivo the 3-dimensional (3-D) geometric architecture of the subtalar and midtarsal joints in normal and rheumatoid arthritic (RA) feet, using magnetic resonance imaging (MRI) analysis.Methods. MRI was performed on 23 patients with RA, all of whom had disease activity in the subtalar and/or midtarsal joints. Image processing techniques were used to create 3-D reconstructions of the calcaneus (C), cuboid (c), navicular (N), and talus (T) bones. Twenty-four standard architectural parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…The architecture of the foot can be disrupted by repeated inflammation of synovial joints and surrounding soft tissues in rheumatoid arthritis (RA) (Bouysset et al, 1987;Jernberg et al, 1999;Woodburn et al, 2002a). In the ankle/rearfoot region this frequently leads to acquired pes planovalgus (flat foot deformity), which is associated with localized pain and stiffness and impaired ambulation (Keenan et al, 1991;Platto et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The architecture of the foot can be disrupted by repeated inflammation of synovial joints and surrounding soft tissues in rheumatoid arthritis (RA) (Bouysset et al, 1987;Jernberg et al, 1999;Woodburn et al, 2002a). In the ankle/rearfoot region this frequently leads to acquired pes planovalgus (flat foot deformity), which is associated with localized pain and stiffness and impaired ambulation (Keenan et al, 1991;Platto et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In the ankle/rearfoot region this frequently leads to acquired pes planovalgus (flat foot deformity), which is associated with localized pain and stiffness and impaired ambulation (Keenan et al, 1991;Platto et al, 1991). Various 2D radiographic and 3D magnetic resonance imaging (MRI) techniques have been used to quantify bony deformity while MRI and ultrasonography have usefully mapped synovial inflammation in the tarsal joints and tendons (Bouysset et al, 1987;Koski, 1993;Lehtinen et al, 1996;Jernberg et al, 1999;Woodburn et al, 2002a). Questionnaire-based tools have determined impaired foot function using metrics for localized pain, ambulation and disability (Platto et al, 1991;Garrow et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Slight hindfoot pronation is common in the general population in weightbearing, and in RA, as a consequence of inflammatory lesions, the soft supporting structures become stretched, leading to midfoot flattening and hindfoot hyperpronation [12]. Subtalar joint synovitis and talonavicular joint synovitis [13], inflammatory posterior tibial tendon dysfunction [14][15][16], and ligament lesions also play a role (talocalcaneal interosseous ligament, spring and long plantar ligament, and joint capsules) [17][18][19][20]. There was no difference in the proportion of cavus feet in the RF and CF groups, while normal feet were significantly less frequent in the RF group, and flat feet were much more frequent.…”
Section: Discussionmentioning
confidence: 99%
“…25 Further, low-field MRI and US were superior to clinical examination for detection of joint inflammation in RA feet. 13,37 Using MRI as the gold standard, Wakefield et al 38 reported that US was more specific in identifying hindfoot and midtarsal joint synovitis and tenosynovitis compared with clinical examination in patients with established RA. Woodburn et al 39 who utilized MRI techniques to compare geometric architecture of subtalar and midtarsal joints in normal and symptomatic feet of 23 RA patients, concluded that only subtalar joint synovitis was predictive of abnormal subtalar and midtarsal architecture.…”
Section: Imaging Of Subtalar and Midfoot Joint Disease In Ramentioning
confidence: 99%